Characterizing crystalline volcanic rock (CVR) deposits from Galiano Island, B.C., Canada: Implications for lithic material procurement at the Dionisio Point locality. (September 2015) - Rorabaugh, Adam N.; Davenport, Nichole S.; Grier, Colin
Abstract: We define the elemental signatures of crystalline volcanic rock (CVR) found within the Dionisio Point archeological locality on Galiano Island in coastal southwestern British Columbia. CVR is the dominant toolstone found in archeological assemblages at Dionisio Point and many other sites in the region. The quality of these materials for chipped stone tool manufacture and use is dependent in part on the silica content, which is highly variable. Basalt is considered a poor quality toolstone due to its low silica content of 45–55%, while andesite, dacite, and rhyolite are considered higher quality materials with silica content above 55%. Elemental composition analyses were performed using WDXRF in the WSU Geoanalytical Lab to determine whether local secondary CVR deposits had high silica content. Results show that low and high quality CVR cobbles were locally available to the precontact communities of the Dionisio Point locality, with basalt being the most abundant. Highlights: Elemental signatures of natural cobble and artifact CVRs examined at Galiano Island, British ColumbiaElemental signatures of natural cobble and artifact CVRs examined at Galiano Island, British Columbia. CVR artifacts and natural cobbles had highly variable quality. Basalt most common in natural set. Evidence of selection for high quality CV in artifacts. High quality CVR was locally available.